Insomnia and psychological disintegration: Evidence from a transdiagnostic network analysis - Niloufar Moohebat; Farhad Khormaei (PLoS ONE, 2026)
Insomnia is commonly conceptualized in terms of hyperarousal or symptom amplification; however, less attention has been paid to the structural organization and integration of psychological processes underlying sleep disturbance. This study examined whether insomnia is associated with reduced integration among psychological domains rather than elevated symptom activation alone. A comparative network analysis was conducted on 27 transdiagnostic psychological markers in a sample of 391 Iranian university students (169 poor sleepers, 222 good sleepers). Gaussian graphical models were estimated using graphical LASSO regularization with EBIC model selection. Network structure, expected influence, and node predictability were examined, and Network Comparison Tests were used to assess structural and global strength differences between groups. Compared with good sleepers, poor sleepers exhibited markedly sparser network structures, a greater number of isolated nodes, and substantially lower node predictability. No significant differences were observed in global network strength between groups. Several cognitive variables tended to show higher centrality in good sleepers, suggesting context-dependent roles within more integrated psychological systems. These findings indicate that insomnia may be characterized by reduced integration among psychological processes rather than uniformly elevated symptom activation, reflecting a systems-level characteristic of psychological functioning associated with sleep disturbance.